ICNP® as care strategy in nursing for a patient with multiple pathologies - Iraktania Vitorino Diniz; Karen Krystine Gonçalves de Brito; Suellen Duarte de Oliveira Matos; Ándrea Cláudia Almeida de Melo Lira; Marta Mirian Lopes Costa; Maria Júlia Guimarães Oliveira Soares (Universidade Estadual de Maringá, 2015)
Current study analyzes an integral care plan for a person with multiple pathologies, using the International Classification for Nursing Practice (ICNP®). The descriptive and observational study, clinical case type, was developed during a home visit to an individual residing in the city of João Pessoa, Paraíba State, Brazil. Eleven nursing diagnosis / results and their respective interventions were outlined following the terms in the ICNP®. Results show that the nurse's role in this context is a practice grounded on the systematization of nursing with the intention of an easy early identification and prevention of damages related to the patient, during nursing visits.